Performance evaluation of industrial systems : discrete event simulation in using Excel/VBA - Elizandro, David. 4 0 16; Taha, Hamdy A.,;Elizandro, David; 5 (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2012)
Discussing fundamental modeling tools, queuing theory, and discrete event simulation for evaluating production systems, this book presents a development environment for discrete event simulation in a language easy enough to use but flexible enough to facilitate modeling complex systems. Incorporating the use of discrete simulation to statistically analyze a system and render the most efficient time-sequences, designs, upgrades, and operations, this new edition develops new visualization graphics for DEEDS software, includes improvements in the optimization of the simulation algorithms, and adds a chapter on queuing models--
Rev. ed. of: Simulation of industrial systems by David Elizandro. c2008.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Microsoft Excel (Computer file);Visual Basic; Evaluation;Data processing.;Data processing. -- Manufacturing processes;Operations research;Microsoft Excel (Computer file).;Visual Basic; 20; 2